Relationship of extreme dry spells in Eastern Mediterranean with large-scale circulation - Oikonomou, C.; H. A. Flocas; M. Hatzaki; Nisantzi, A.; Asimakopoulos, D.N. (Theoretical and Applied Climatology, 2010)
The relationship of prolonged dry spells in Eastern Mediterranean with large-scale surface and upper circulation is investigated on seasonal basis with the aid of the Singular-Value Decomposition Analysis (SVDA) for the period 1958-2000. The study was based on daily precipitation data of 56 stations, evenly distributed over Eastern Mediterranean region. Extreme dry spells are defined using the CDD index (maximum number of consecutive dry days). It was found that teleconnection patterns centered over Northern Atlantic and northern Europe seem to affect the duration of the longest dry spells over the Eastern Mediterranean, while surface synoptic scale systems in Northern Africa play a substantial role. The SVDA results compare well with the corresponding results of Canonical Correlation Analysis (CCA), mainly for the surface circulation during winter and summer. © Springer-Verlag 2009.
Keywords: Atlantic Ocean; Atlantic Ocean (North); atmospheric circulation; canonical analysis; dry season; Europe; Mediterranean Region; summer; Synoptic meteorology; teleconnection; winter